Pengaruh Fitur Paylater terhadap Sifat Belanja yang Konsumtif pada Remaja di Kota Batam - Reddyson Reddyson; Franky Franky; Handyca Yeng; Vicco Leonardo; Leonardy Leonardy (LPPM Universitas BSI, 2022)
Paylater is a digital payment feature used on e-commerce that act like credit card, which allowed us to pay later, like its namesake. The motivation to buy goods among teenagers is very lacking because the current economic conditions are still unstable, so that the paylater feature can help encourage the motivation to buy goods in the community or teenagers do not make payments directly but gradually. The purpose of this study is to test how much the use of the paylater system encourages impulsive purchases so that people use the paylater feature as a payment medium. The method used is using quantitative methods, namely by using questionnaires distributed to respondents then collecting and analyzing data from respondents, as many as 289 respondents were involved in this research. By using the method of Structural Equation Modeling (SEM) with SPSS AMOS software. This study found that interpersonal and External Factors had a large and positive effect on hedonic and utilitarian motivation, hedonic motivation had no significant effect on impulsive buying, while utilitarian motivation had a significant effect on impulsive buying, and an effective paylater was related to hedonic motivation and impulsive buying. The use of the Paylater feature can be a solution because it can encourage motivation in impulse purchases to meet needs without burdening their financial situation so that Paylater users still have a stable economy.Keyword: Paylater, E-commerce, Impulse buying